Electric, swashplate-less individual blade control system to be wind tunnel tested in full-scale - Arnold, U.T.P.; Sutton, C. (My University, 2019)
This paper describes a novel principle of helicopter main rotor primary control, which is scheduled to be demonstrated within a full-scale wind tunnel test campaign. The presented concept uses individual high performance electrical actuators to control the pitch angle independently for each rotor blade. Thereby many limitations of conventional hydraulic control systems are overcome and new functionalities can be introduced which largely improve the rotor performance and attenuate its inherent limitations. First, the rationale behind that idea and the basic concept is described. Then the chosen test platform is introduced and its unique suitability for this technology is highlighted. The key requirements that have primarily driven the design are presented. Further, the practical realization and the system integration into the test rotor is detailed. Key components such as the actuator, actuator control unit and power electronics are described in more detail. Finally, the preparatory test setup in the System Integration Lab (SIL) test is discussed.